PENERAPAN PEMBELAJARAN REFLEKTIF DALAM UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN SEPAK BOLA SISWA KELAS XI IPA 1 SMA NEGERI 1 UNGARAN KABUPATEN SEMARANG TAHUN 2013/2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
Purpose of this study was to determine whether reflective learning to improve critical thinking skills that affect student learning outcomes soccer SMA Negeri 1 Ungaran . This study is an action research ( PTK ) in which there are two siklus. Methods of data collection used in this study is the use data collection techniques such as tests and observasi.Instrumen used are lesson plans, observation sheets and test data used praktik.Teknik analysis is quantitative and qualitative data . Results showed before applying reflective learning or students who completed the initial data is only 19.35 % . Once applied reflective learning in learning football on students who complete the first cycle of 51.61 % , so there is an increase of the initial data with a percentage of 32.26 % . In the second cycle the number of students who pass with a percentage of 87.09 % , and an increase of 35.48 % for the first cycle . Based on the results of this study concluded that the application of reflective learning on learning football can improve critical thinking skills that effect on increasing student learning achievement soccer class XI IPA 1 SMAN 1 Ungaran.